Advances in Computing and ALS: Reflections on Directions for Enhancing the Quality of Life - Horvitz, Eric (International Symposium on ALS/MND in Birmingham, UK, 2008)
Invited Talk Creative application of computing... Human-computer interaction Machine learning & intelligence Connectivity & content Robotics … to enhance the quality of life of people with ALS.